Communication management in the sister village program: Mount Merapi disaster mitigation efforts with a participatory approach - Yani Tri Wijayanti; S Bekti Istiyanto; Tri Susanto; Handini Handini; Irwanto Irwanto (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
The 2010 eruption of Mount Merapi led the Disaster Management Agency (BPBD) of Magelang Regency to implement the Sister Village Program as a participatory disaster mitigation strategy. This study aims to examine how communication was managed to support this initiative, focusing on audience identification, goal setting, message planning, and channel selection. Using a qualitative case study approach, data were collected through participatory observation and in-depth interviews with BPBD officials, village leaders, and residents from both disaster-prone and buffer villages. Findings show that the integration of local knowledge, structured dialog through the three plano papers, and inclusive stakeholder engagement played a critical role in enhancing preparedness and response. The study highlights that communication strategies rooted in community-driven practices foster trust, coordination, and timely evacuation. These results suggest that participatory communication management is essential for effective disaster mitigation and should be adapted to other disaster-prone areas in Indonesia.